QUALITY OF SERVICE ROOM ATTENDANT AT HARRIS RESORT WATERFRONT BATAM RIAU ISLAND - Vira Islamiati; Andi M Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Riau Islands Province is the second gateway for foreign tourists after Bali. Batam City which supports Indonesia from various sectors such as the hotel sector. By providing accommodation, tourists can enjoy a very comfortable vacation. In a hotel, the department that plays a role in providing hotel guests, especially regarding service comfort, cleanliness of the entire hotel area is housekeeping. In this case, HARRIS Resort Waterfront Batam, Riau Islands, develops the comfort that guests get by conducting a survey on service quality. The purpose of this study is to determine the quality of Room Attendant services in improving the services that will be provided to guests. The method used in this study is a quantitative method to find out the results of the survey through observation, distributing questionnaires to respondents/guests who have stayed at the hotel, and based on the documentation of several guests who have provided answers through the questionnaire. Based on the survey and the results of data processing that has been carried out, the authors get the data from the recapitulation results, it can be seen that the total score of Room Attendant Service Quality at HARRIS Resort Waterfront Batam, Riau Islands is 7177 where the results range from a total score of 7140-8500 into the